Basic organic chemistry for the life sciences - Vancik, Hrvoj (Springer International Publishing, 2014)
This work provides an overview of the basics of organic chemistry for non-chemists. As such, this book should be very useful for university students of biology, molecular biology, ecology, medicine, agriculture, forestry, and other specialties where the knowledge of organic chemistry plays the important role but is not a core discipline. The book should also be of interest to non-professionals, and it may serve as a manual or repetitorium to high school teachers.   The text is divided into eleven chapters on the basis of the systematization of fundamental organic reaction types, and classes of organic compounds. The first chapters comprise fundamental aspects of structural theory, reaction mechanisms, electronic structure, some basic spectroscopy, and properties of main groups of organic compounds. At the end of the book, the largest chapter contains the elements of the organic chemistry of natural products. Comparison of the reactions in the laboratory with the analogous molecular transformations in living cells will enable the reader to better understand the basic principles of biochemistry.